Organic carbon dynamics in soils with pyrogenic organic matter that received plant residue additions over seven years. (September 2015) - Dharmakeerthi, R. Saman; Hanley, Kelly; Whitman, Thea; Woolf, Dominic; Lehmann, Johannes
Abstract: The effect of repeated application of plant residues on mineralization of different organic carbon (OC) pools in a pyrogenic organic matter (PyOM) amended soil was determined using an incubation study conducted over 7.1 years. At five occasions during this period, sugarcane residues (C4 ) were mixed with the soil (C4 ) with or without PyOM (C3 ) amendments. Organic C mineralized during the incubation period or remaining in different physical soil fractions after 7.1 years was partitioned into PyOM carbon (PyOM-C) and native soil organic matter C (nSOM-C) or sugarcane C plus nSOM-C (SC-C + nSOM-C). When compared to the control, total cumulative OC (comprising both nSOM-C and PyOM-C) mineralized in the presence of PyOM was 40% higher after the first 2.5 years, but equal by 6.2 years and 3% lower by the end of the incubation period. The cumulative nSOM mineralization after 7.1 years was 2.57 mg CO2 –C g −1 soil with PyOM compared to 3.16 mg CO2 –C g −1 soil without PyOM addition (p = 0.13; n = 3). More than 60% of the added PyOM-C was present in the free-light fraction by the end of the 7.1 years. In total, 93% of the added PyOM-C remained in soil compared to 25–28% of SC-C + nSOM-C. Sugarcane residues increased the remaining PyOM-C in the occluded-light fraction by 3% (p < 0.05) and in the organo-mineral fraction by 4% (p < 0.1), suggesting a possible preferential use of SC-C or accumulation of metabolites of decomposed PyOM. However, the addition of sugarcane had no significant effect on overall mineralization of PyOM. The presence of PyOM accelerated the mineralization of SC-C + nSOM-C by 9% (p < 0.001). This is probably due to enhanced mineralization of sugarcane residues rather than native SOM. Although PyOM was likely to accelerate mineralization of added plant residues throughout a 7-year period, PyOM did not increase cumulative nSOM mineralization when plant residues were absent (p > 0.05), so PyOM may reduce nSOM mineralization in the long term. Highlights: Mineralization of native SOM (nSOM) increased in the first year after PyOM additions. Cumulative nSOM mineralization remained unchanged seven years after PyOM additions. PyOM mineralization was unaffected by repeated residue application over seven years. PyOM contents within aggregates increased with crop residue applications.